PENINGKATAN KINERJA PERSEDIAAN PRODUK DI PT. PROPAN RAYA I.C.C SURABAYA - Prakoso, Yuki Tejo; Yuliawati, Evi (Jurnal Ilmiah Teknik Industri, 2013)
Inventory control is an internal process that is essential for the companys operations, especially in the field of industrial paints. Many types, colors and sizes of packaging paint often urged companies to hoard supplies. Nevertheless the possibility of failing to meet customer demand still occur, either due to exhaustion of stock, delivery delays, or for any other reason. Finished product inventory control in a way or innovative method must be developed to reduce excess inventory so as to minimize storage costs and to meet customer needs optimally. Use the ABC method and modifications VEN can be an alternative in inventory control application based on the classification of products and level of service companies. With a combination of ABC-VEN method, it will obtain 9 grade product inventory to the value of each service level that has been adjusted so that it can help determine the optimal inventory control policies for the company. From the research, suggested inventory control policy indicates that the inventory turnover rate suggested an average 3.14 times per year is the number of days supply of inventory was 76 days.This means that the inventory control policy suggested, PT. Propan Raya I.C.C can improve inventory performance by increasing the speed of inventory turnover amounted to 60.2% and increase the efficiency of the number of days supply of inventory by 37.7% of the current inventory.